Menelusuri Jejak Spiritualitas dalam Pembelajaran Kaligrafi Metode Hamidi di Pesantren SAKAL Jombang - Ashoumi, Hilyah; Rahman, Zayad Abd; Ahid, Nur; Kholid, Abdul (Lembaga Penelitian dan Pengabdian pada Masyarakat, Institut Agama Islam Negeri (IAIN) Kerinci, Jambi, 2025)
This study aims to explore the quality indicators of calligraphy within the implementation of the Hamidi Method, as well as to trace the spiritual dimensions embedded in the calligraphy learning process at SAKAL Islamic Boarding School (Pesantren) in Jombang. Using a qualitative approach, this research analyzes how technical aspects—such as proportional accuracy (nisbah), consistency of letterforms, and artistic composition—are harmoniously integrated with spiritual values, making each stroke of calligraphy a form of devotion to the Divine Word (Kalamullah). The Hamidi Method is implemented progressively through the use of kurrasah (instructional booklets) and scholarly mentorship rooted in a chain of transmission (sanad), developing students'skills while instilling discipline and Islamic spirituality.The indicators of calligraphy quality in this context include five key aspects: proper use of tools and materials, technical precision, harmonious layout composition, fluency in writing, and artistic expression grounded in tradition. From Seyyed Hossein Nasr’s perspective on spirituality, calligraphy is not merely visual art but sacred art that fulfills four main functions: psychological-spiritual balance, reminder of Divine transcendence, reflection of collective religious consciousness, and a symbol of Islamic civilizational progress. The findings indicate that the Hamidi Method is not only effective for technical skill development but also serves as a transformative educational model that blends spirituality and culture, bridging classical Islamic values with contemporary relevance.